Dampak Dana Desa terhadap Pertumbuhan dan Perkembangan Ekonomi Regional di Indonesia - A.A. Ngurah Gede, Wasudewa; Iskandar, Doddy Aditya (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2023)
Indonesia’s economic development inclusiveness accomplishment is relatively low. Mainly on economic’s growth and development. This is partly due to the orientation of past development which tends to be centralized. Since this centralized paradigm has diverted to decentralization, especially during the implementation of the village fund granting policy, it is necessary to examine the actual impact. This is a prominent issue considering that the implementation of village fund distribution has been running for more than five years and enough funds have been disbursed. Hence the purpose of this study is to measure the impact of providing village funds on the achievement of economic growth and development in Indonesia. The method used is a quantitative approach, with the technique of Difference-in-Difference (DID) analysis. The results of this study show that the provision of village funds is empirically proven to be able to positively accelerate the achievement of economic growth and development in a region in Indonesia. Thereupon the provision of village funds must remain consistently provided by continuing to seek various forms of improvement in its implementation